2020
DOI: 10.1016/j.conbuildmat.2019.117806
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive models for fibre reinforced soil bricks

Abstract: In this paper, the physical, durability and mechanical properties of soil bricks reinforced with chicken feather fibres (CFF) and sugarcane bagasse fibres (SBF) were studied. The adopted optimum lengths of 15-mm of CFF and SBF were randomly distributed in the soil mix at 1%, 3%, 5%, 7%, 9% and 11% by weight. In total, 525 samples of cubic (350) and prismatic (175) soil samples were prepared for each fibre type and tested in accordance with the guidance in the British standards for bulk density, water absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
(53 reference statements)
0
24
0
5
Order By: Relevance
“…In Danso et al (2015), SBF was added and yielded a product with compressive strength ranging between 1.07 MPa-1.13 MPa. Similarly, Salih et al (2020) showed that adding SBF increased compressive strength and obtained values between 1.82 MPa-3.98 MPa.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…In Danso et al (2015), SBF was added and yielded a product with compressive strength ranging between 1.07 MPa-1.13 MPa. Similarly, Salih et al (2020) showed that adding SBF increased compressive strength and obtained values between 1.82 MPa-3.98 MPa.…”
Section: Resultsmentioning
confidence: 86%
“…Adding fiber to a clay mixture forms a bond, and this addition is responsible for compressive transmission in soil. This effect is called the fiber bridging mechanism (Salih et al, 2020). This can be seen in the SBF-containing samples, which had higher compressive strength ratings compared to the C and X samples.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations